The Bottom-Up Rise Strength Transfer in Elderly After Endurance and Resistance Training: The BURST - Pietrangelo, Tiziana; Bondi, Danilo; Kinel, Edyta; Verratti, Vittore (Frontiers in Physiology, 2019)
The phenomenon of cross-education is well-known related to the homolateral – contralateral influence. Recent concepts of “exerkines” and “exersomes”, together with to the framework of low-grade inflammation, drive the interest towards the comprehension of exercise-related cross-talk between distant tissues. In order to relate the systemic effects to the worthy field of healthy aging, providing a functional background for further speculations, we recruited 31 healthy old males and investigated the effect of endurance and resistance training (ET and RT) protocols vs. control on a 12 weeks ex-post comparison. The participants underwent anthropometric assessment – BMI, plicometry, thigh circumferences - and functional evaluation – Maximal Voluntary Contraction (MVC) on quadriceps and Handgrip Strength (HS). No significant difference was found for BMI, plicometry and circumferences. Statistical analyses revealed a significant improvement in all the two functional tests, with post-hoc independent effect for RT on MVC and for ET on HS. We demonstrated the cross-education effect from lower to higher limbs, calling it Bottom-Up Rise Strength Transfer (BURST).This effect can be related to systemic factors, likely circulating myokines and extracellular vesicles, whit an eventual concomitant reduction of a low-level sub-clinical chronic inflammation. Further studies are needed to better characterize the exercise-related cross-talk, concerning the specificity of different protocols and the involved physiological pathways, improving the intervention for training, prevention and rehabilitation.